Produção de biocatalisadores multi-ativos através da co-imobilização camada sobre camada de lipase a lacase utilizando diferentes suportes. - Amorim, Kímberle Paiva dos Santos (2022)
The tandem use of different enzymes is commonly necessary to accomplish a whole process, such as for compounds synthesis and for degradation of pollutants from industrial effluents, for example. Lipases and laccases can co-collaborate to the synthesis of pharmaceuticals, some polymers and enantiomerically enriched compounds, for example, and in bioremediation. Immobilization of enzyme helps to overcome some limitations related to their instability and difficult to reuse. In this work, two materials (agarose and cellulose) were tested as support for lipase and laccase co-immobilization through a layer-by-layer strategy, using polyethyleneimine as a glue between enzyme layers. Lipase from Pseudomonas fluorescenes (used for both materials), laccase from Aspergillus sp. (for agarosed based support), and laccase from Trametes versicolor (for cellulose based supports) were chosen for this study due to their well-recognized catalytic performances. Firstly, porous materials based on agarose ― DEAE and octyl agarose (OA) ― were tested as supports for the co-immobilization. OA showed to be the most appropriate, providing a multi-active and highly thermally stable biocatalyst (keeping 100% of lipase activity after 48h at 50 ºC, pH 7). Mass transfer studies showed that it was possible to obtain heterogeneous biocatalysts with activity of 88.59 ± 1.0 U/g for lipase and 51.14 ± 1.31 U/g for laccase without internal diffusional limitations. Secondly, supports based on cellulose nanocrystalline (CNC) were tested for the same layer-by-layer strategy previously studied. FTIR and SEM assays demonstrated the chemical and morphological changes caused by the functionalizations performed on this support. Then, the first layer of enzyme (lipase) was immobilized using CNC and CNC functionalized with aldehyde, which produced biocatalysts with distinct characteristics (activity and stability). Functionalized CNC obtained through periodate oxidation (CNCox) showed to be the support providing a biocatalyst with higher activity (16.01 ± 1.05 U/g when 1.7 mg/g of protein load was used for immobilization) and stability (t1/2 = 9.86 ± 1.94, at 60 ºC). Thus, CNCox was used as support for the co-immobilization, which produced a multi-active biocatalyst with improved thermal stability, with co-immobilized lipase keeping more than 90% of its activity along 48 h of incubation at 50 ºC. Besides, it could be applied in recyles of reactions using standard substrates of both enzymes. The multi-active biocatalysts produced in this work using different supports present a great potential to be applied in multi-enzymatic systems of industrial interest.